Longitudinal analysis of the genetic and environmental influences on components of cognitive delay in preschoolers - Eley, T; Dale, P; Bishop, D; Price, T; Plomin, R (American Psychological Association, 2001)
The etiology of verbal and performance delays were investigated in a large population sample of twins at 2 and 3 years (N = 2,449 pairs). These data replicate and extend earlier analyses at 2 years (T. C. Eley et al., 1999). Several ways of defining delay were compared, selecting from the lowest 5% of the sample on both verbal (V) and performance (P) measures. V delay with or without P delay was highly heritable (.93 and .62, respectively), whereas P delay without V delay was less heritable (.29), with substantial shared environment influence (.48). Longitudinal genetic analyses indicated substantial heritability of V delay from 2 to 3 years, especially in combination with P delay (.48 and .81, respectively). Similarly, genetic influence on continuity of P delay without V delay was much lower (.22). These results suggest that it is useful to consider the strong genetic contribution to verbal delay regardless of nonverbal impairment in preschoolers.